The Resistance of Oilseed Rape Microspore-Derived Embryos to Osmotic Stress Is Associated With the Accumulation of Energy Metabolism Proteins, Redox Homeostasis, Higher Abscisic Acid, and Cytokinin Contents - Urban, Milan O.; Planchon, Sébastien; Hoštičková, Irena; Vanková, Radomira; Dobrev, Peter; Renaut, Jenny; Klíma, Miroslav; Vítámvás, Pavel (Frontiers in Plant Science, 2021)
The present study aims to investigate the response of rapeseed microspore-derived embryos (MDE) to osmotic stress at the proteome level. The PEG-induced osmotic stress was studied in the cotyledonary stage of MDE of two genotypes: Cadeli (D) and Viking (V), previously reported to exhibit contrasting leaf proteome responses under drought. Two-dimensional difference gel electrophoresis (2D-DIGE) revealed 156 representative protein spots that have been selected for MALDI-TOF/TOF analysis. Sixty-three proteins have been successfully identified and divided into eight functional groups. Data are available via ProteomeXchange with identifier PXD024552. Eight selected protein accumulation trends were compared with real-time quantitative PCR (RT-qPCR). Biomass accumulation in treated D was significantly higher (3-fold) than in V, which indicates D is resistant to osmotic stress. Cultivar D displayed resistance strategy by the accumulation of proteins in energy metabolism, redox homeostasis, protein destination, and signaling functional groups, high ABA, and active cytokinins (CKs) contents. In contrast, the V protein profile displayed high requirements of energy and nutrients with a significant number of stress-related proteins and cell structure changes accompanied by quick downregulation of active CKs, as well as salicylic and jasmonic acids. Genes that were suitable for gene-targeting showed significantly higher expression in treated samples and were identified as phospholipase D alpha, peroxiredoxin antioxidant, and lactoylglutathione lyase. The MDE proteome profile has been compared with the leaf proteome evaluated in our previous study. Different mechanisms to cope with osmotic stress were revealed between the genotypes studied. This proteomic study is the first step to validate MDE as a suitable model for follow-up research on the characterization of new crossings and can be used for preselection of resistant genotypes.